Pola Pengelolaan Pendidikan Anak Usia Dini di PAUD Ceria Gondangsari Jawa Tengah - Rohmah, Nur; Fatimah, Dyah Fifin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
This research began from the writer’s interest on the distinctive characteristic of early childhood education at PAUD Ceria. It is interesting because regardless the academic qualifications of its’ teachers, students demonstrate good academic performance, as well as parents and community’s support for the existence of this PAUD. This research aims at analyzing the patterns in early childhood education management especially that of planning,organizing, actuating, and controlling, and to examine community’s shifting paradigm about childhood education. This is a qualitative research that was undertaken in PAUD Ceria, Gondangsari, Sumawono, Central Java. The data gathered through observation, interview and documentation. This research shows that: 1). PAUD Ceria uses POAC management pattern in every activities, such as planning at the beginning, building communication and cooperation with stakeholders in organizing phase, while integrating religious education materials within actuating process. Whereas, controlling process is conducted everyday. 2). Supporting factors in the management of early childhood education are: students motivation, cooperation between teachers, community support, open comunication between teachers and parents, and cooperation with government. Finally 3). The result of management pattern at PAUD Ceria such as studet achievements in many championships, the increment of students enrollment each year, and change communnity’s paradigm on the importance of early childhood education.